Could State-Controlled Media Stabilize the Market during the U.S.-China Trade Frictions? - Wenjia Zhang; Julan Du (Credit and Capital Markets – Kredit und Kapital, 2022)
The China-U.S. trade frictions brought about many uncertainties to the Chinese economy. This research investigates whether China's state-controlled media played a role in stabilizing investors' expectations by examining the relations between media tone and Chinese stock market reactions in the context of China-U.S. trade frictions. Firstly, even though the media tone of news on trade frictions did not elicit significant reactions at the market level, those firms heavily exposed to export business with the U.S. produced significant positive reactions to a high media tone of the state media. Secondly, investors, especially SME investors, perceived more uncertainties to the high tones of Chinese media in the early days of Trump's presidency and reacted negatively to the media's high stance, as shown in the volatility. Thirdly, after the war was initiated, higher-tone news released from the state-controlled press eased people's anxieties and stabilized the market, especially for the large caps, leading to lower volatilities in most subsequent stages. Generally, the official media's tone manipulation is partially effective in preventing a market meltdown and easing investors' worries.
Keywords: E44; 330; State-controlled media; Media tone; U.S.-China Trade Frictions; E 44